A one-pot catalyst-free synthesis of functionalized pyrrolo[1,2-a]quinoxaline derivatives from benzene-1,2-diamine, acetylenedicarboxylates and ethyl bromopyruvate - Piltan, Mohammad; Moradi, Loghman; Abasi, Golaleh; Zarei, Seyed Amir (Beilstein Journal of Organic Chemistry, 2013)
The catalyst-free multicomponent reaction of 1,2-diaminobenzene, dialkyl acetylenedicarboxylates, and ethyl bromopyruvate forms pyrrolo[1,2-a]quinoxaline derivatives in good yields. Ethylenediamine also reacts under similar conditions to produce new pyrrolo[1,2-a]pyrazine derivatives.
Keywords: acetylenedicarboxylates; benzene-1,2-diamine; ethyl bromopyruvate; pyrrolo[1,2-a]pyrazine; pyrrolo[1,2-a]quinoxaline